The carbon starvation response of the ectomycorrhizal fungus Paxillus involutus - Ellström, Magnus (FEMS Microbiol Ecol, 2015)
The amounts of carbon allocated to the fungal partner in ectomycorrhizal associations can vary substantially depending on the plant growth and the soil nutrient conditions, and the fungus may frequently be confronted with limitations in carbon. We used chemical analysis and transcriptome profiling to examine the physiological response of the ectomycorrhizal fungus Paxillus involutus to carbon starvation during axenic cultivation. Carbon starvation induced a decrease in the biomass. Concomitantly, ammonium, cell wall material (chitin) and proteolytic enzymes were released into the medium, which suggest autolysis. Compared with the transcriptome of actively growing hyphae, about 45% of the transcripts analyzed were differentially regulated during C-starvation. Induced during starvation were transcripts encoding extracellular enzymes such as peptidases, chitinases and laccases. In parallel, transcripts of N-transporters were upregulated, which suggest that some of the released nitrogen compounds were re-assimilated by the mycelium. The observed changes suggest that the carbon starvation response in P. involutus is associated with complex cellular changes that involves autolysis, recycling of intracellular compounds by autophagy and reabsorption of the extracellular released material. The study provides molecular markers that can be used to examine the role of autolysis for the turnover and survival of the ectomycorrhizal mycelium in soils.